Globalisation versus westernisation : the case of education / Patrick Tourchon and Leniiw Roman - Patrick, Tourchon; Leniiw, Roman (Universiti Teknologi MARA, Sarawak, 2001)
Now that globalisation has become a key concept, it calls for a strict definition. But too narrow a reading of such a definition can cause important trends to be overlooked. By interpreting the notion of globalisation in a wider, though still formal, way, this article aims at examining some aspects of global education seldom discussed so far. In particular, it stresses the original and leading part Asia can play in the process.